"Breaking Her Spirit" Through Objectification, Fragmentation, and Consumption: A Conceptual Framework for Understanding Domestic Sex Trafficking. Issue 6 (3rd July 2018) - Herrington, Rachael L.; McEachern, Patricia
ABSTRACT: It is now recognized that sex trafficking is an issue present in the United States as victims are frequently children and adults who were born and raised in the United States. Anti-trafficking researchers and advocates state that the problem is one of supply and demand and that trafficking of vulnerable individuals will continue until the demand for commercial sex ceases. One goal of this article is to show how Carol Adams' model of violence against women is uniquely applicable to the issue of sex trafficking. In particular, this article outlines the ways in which objectification, fragmentation, and consumption allow commercial sexual exploitation through sex trafficking to continue. The article also explores links between pornography and sex trafficking as well as the processes traffickers use to groom individuals for exploitation through prostitution in a manner that helps to ensure compliance. Finally, the article seeks to implore clinicians to increase their understanding of the issues unique to sex trafficking survivors and take an integrative theoretical approach when working with trafficked individuals.